The Influence of Self Efficacy and Emotional Intelligence on Employee Performance through Job Satisfaction at PT. Telkom Indonesia Regional 1 Sumatera - Muhammad Haris; Paham Ginting; Yeni Absah (Proceeding of The International Conference on Business and Economics, 2024)
This research aims to see the extent to which Self efficacy and emotional intelligence affect employee performance with job satisfaction as an intervening variable at PT. Telkom Indonesia Regional 1 Sumatra. The sample selection technique used random sampling and a sample of 42 respondents was obtained. Data analysis techniques use multiple regression analysis and path analysis. From the results of the hypothesis test it can be concluded that Self Efficacy has a positive and significant effect on Job Satisfaction at PT. Telkom Indonesia Regional 1 Sumatra. Emotional Intelligence does not have a significant effect on Job Satisfaction at PT. Telkom Indonesia Regional 1 Sumatra. Self Efficacy has a positive and significant effect on Employee Performance at PT. Telkom Indonesia Regional 1 Sumatra. Emotional Intelligence has a positive and significant effect on Employee Performance at PT. Telkom Indonesia Regional 1 Sumatra. Job Satisfaction does not have a significant effect on Employee Performance at PT. Telkom Indonesia Regional 1 Sumatra. Self Efficacy does not have a significant effect on Employee Performance through Job Satisfaction at PT. Telkom Indonesia Regional 1 Sumatra. Emotional Intelligence has no effect on Employee Performance through Job Satisfaction at PT. Telkom Indonesia Regional 1 Sumatra.